THE EFFECT OF ANTENATAL YOGA ON LOW BACK PAIN IN THIRD-TRIMESTER OF PREGNANCY - Salva Dwi Kosayriyah; Kholisotin Kholisotin; Zainal Munir; Handono FR; Abdul Hamid Wahid (Journal of Maternity Care and Reproductive Health, 2020)
Low back pain is pain that occurs in the lumbosacral region and would get worse with increasing the gestational age. The purpose of this study was to determine the decrease of the low back pain before and after doing antenatal yoga. The design of this study was quasy experiment study using unequal control groups, the group divided into experimental and control groups. The study was conducted at BPM Hj. Suharni Cermee Bondowoso, the number of respondent was 50 pregnant women that chosen using a purposive sampling technique. The instrument used an observation sheet. In this study yoga was performed 4 times in 2 weeks with a duration of 1 hour per session. Data analysis using the Paired T-Test. Statistical results showed the value of p = 0,000 <0.05. There is a significant effect of antenatal yoga to the low back pain scale in the third trimester of pregnant women.Keywords: Low back pain, pregnant women, antenatal yoga.